Enabling endangered species conservation on private land: A case study of the ocelot in Texas - Lindsay A. Martinez; Tyler A. Campbell; Roel R. Lopez (Wildlife Society Bulletin)
Abstract The ocelot (Leopardus pardalis) is a wild cat distributed from the southern U.S. to northern South America. In the U.S., ocelots are classified as endangered, and breeding ocelot populations are only found in Texas—a state composed of mostly private lands. Ocelot recovery in the U.S. depends on successful conservation actions on private lands. Unfortunately, throughout the history of the Endangered Species Act (ESA), listed species conservation on private lands has often been plagued by poor landowner participation due to fear of ESA regulations impacting land use. Here, we examine an effort to accelerate the recovery of the ocelot by reintroducing the endangered cat to private lands within its historic range in Texas. The case study of the planned ocelot reintroduction on private lands in Texas, combined with review of literature on ESA implementation on private lands, has illustrated key factors for enabling private landowner engagement in threatened and endangered species recovery. Such factors include providing financial incentives and regulatory assurances to landowners, connecting to landowners’ intangible motivations to conserve wildlife, meeting the practical needs of conservation project implementation while still giving landowners autonomy over the effort, maximizing landowner comfort with a conservation program, and allowing participation to be nonpermanent and adaptable. Over the next 50 years of ESA implementation, these will be important considerations for accelerating species sustainment and recovery efforts on private lands.